Negation, subjectivity, and the history of rhetoric - Vitanza, Victor J. (Albany State University of New York Press, 1997)
Vitanza introduces his book with the questions: "What Do I Want, Wanting to Write This ('our') Book? What Do I Want, Wanting You to Read This ('our') Book?" Thereafter, in a series of chapters and excursions and as schizographer of rhetorics (erotics), he interrogates three recent, influential historians of Sophists (Edward Schiappa, John Poulakos, and Susan Jarratt), and how these historians as well as others represent Sophists and, in particular, Isocrates and Gorgias under the sign of the negative. Vitanza concludes - rather rebegins in a sophistic-performative excursus - with a prelude to future (anterior) histories of rhetorics. Vitanza asks: "What will have been anti-Oedipalizedized (de-negated) hysteries of rhetorics? What will have they looked like, sounded, read like? Or to ask affirmatively, what, then, will have libidinalized-hysteries of rhetorics looked, sounded, read like?"
Introduction: What Do I Want, Wanting to Write This ("our") Book? What Do I Want, Wanting You to Read This ("our") Book? -- Ch. 1. The Sophists? -- Excursus: The Negative, Aesthetics, and the Sublime (terror) -- Ch. 2. Helen(ism)? -- Ch. 3. Isocrates, the Paideia, and Imperialism -- Ch. 4. Isocrates, the Logos, and Heidegger -- Ch. 5. Heidegger, Wesen, and "The Rector's Address" -- Excursus. A Feminist Sophistic? -- Ch. 6. Gorgias, Accounting, and Helen -- Ch. 7. Gorgias, "Some More," and Helens -- Excursus. Preludes to Future (anterior) Histories of Rhetorics (From the Obsessive to the Hysterical and Third Schizo turns)
Includes bibliographical references (pages 393-417) and index.
Keywords: Rhetoric -- History; Rhetoric -- Philosophy; Negation (Logic); Subjectivity; Sophists (Greek philosophy)